Prion strain adaptation: breaking and building species barriers - Reid, Crystal Meyerett, author; Zabel, Mark, advisor; Hoover, Edward, committee member; Spraker, Terry, committee member; Fails, Anna, committee member (Colorado State University. Libraries, 2014)
Prions have been an enigma to researchers and agricultural producers alike since their inception. The timing and order of prion disease discovery can be attributed to the scrutiny of the prion protein-only hypothesis. The characterization of bacteria, viruses, and the infectious qualities encoded by their genomes only confounded the hypothetical notion of protein as an infectious agent. Perhaps viral etiology theories could have been disregarded earlier if genetic prion diseases were not quickly overshadowed by experimental transmissibility of the putative infectious protein. Despite the discordant journey, mounting evidence suggests that prion pathogenesis is caused by the conversion of the normal cellular host protein, (PrPC) into a protease-resistant, abnormal disease-causing isoform devoid of nucleic acid (PrPRES). Importantly, no differences are observed in the primary sequence of PrPC as compared to PrPRES indicating that observable differences between the normal and disease-causing proteins must be conformational. Additionally, even in the absence of nucleic acid, prions are able to infect various hosts differently, suggesting the phenomenon of prion strains. Characteristically long incubation periods and incomplete attack rates, as consequence of primary passage of prion infected material between differing species, but often even within the same species, have been defined as the species and transmission barrier respectively. Conversion efficiency of infectious prions is most efficient when host and donor PrPC are identical leading some researchers to believe that heterologous PrP blocks conversion, extending the days to onset of clinical disease. Evidence also suggests that prion protein primary sequence predisposes PrPC to fold in an un-infectious normal conformation but interaction with a PrPRES conformer, enciphering biological strain characteristics, provides a template for misfolding PrPC into an infectious conformation. Protein misfolding cyclic amplification (PMCA) has provided additional evidence that PrPRES acts as a template that can convert normal prion protein (PrPC) into the infectious misfolded PrPRES isoform. PMCA utilizes sonication to break up PK resistant aggregates into smaller prion seeds that may interact and template PrPC substrate present in the uninfected brain homogenate. Uniquely, prion disease can be inherited, transmitted, or occur spontaneously. Recently, several investigators have reported spontaneous generation of infectious prions using in vitro methods such as PMCA. Additional investigations into host factors needed for efficient conversion and replication has led to the discovery of differences in the propensity of PrPC misfolding among different species. Several groups have recently suggested that cervid prion protein has a higher propensity for misfolding in vitro and in vivo as a result of a unique rigid loop identifiable in cervid PrPC secondary structure. It has been proposed that increased transmission efficiency of cervid prions can be attributed to the presence of this rigid loop. The principle interest in the current research of this dissertation is to gain deeper knowledge about what fundamental factors play a role in prion strain adaptation, to challenge current theories about prion strain fidelity and to assess species barriers and prion strain dynamics with the aid of differential mouse models of prion disease. The comprehensive hypothesis of this dissertation is that host factors, including but not solely PrPC, mediate prion strain adaptation and determine host range and strength of species barriers. We used PMCA, bioassay using transgenic mice expressing variable amounts of PrPC from mouse and cervid species, and cell culture lines expressing different host PrPC to address these questions. We challenged the efficiency and congruency of PMCA by characterizing strain properties of amplified material in parallel with mouse bioassay by: incubation period, PK resistance, glycoform ratios, lesion profiles, and conformational stability. We further wanted to test if PMCA de novo generated prions were infectious and what strain properties they would emulate. We hypothesized that the PK resistant material generated with PMCA was infectious and transmissible and possess strain properties reminiscent of other cervid prion strains. Finally, our lab hypothesized that PrPRES conformation enciphers prion strain properties by acting as a template for nascent PrPRES but that host factors also play a role in adapting prion strains derived from a different host and that species barriers can be overcome through this adaptation.
Keywords: strain adaptation; chronic wasting disease; prion; scrapie